2011
DOI: 10.1007/s00438-011-0665-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of reference genes for gene expression studies in peanut by quantitative real-time RT-PCR

Abstract: Quantitative real-time reverse transcription PCR (qRT-PCR), a sensitive technique for quantifying gene expression, depends on the stability of the reference gene(s) used for data normalization. Only a few studies on the reference genes have been done with peanut to date. In the present study, 14 potential reference genes in peanut were evaluated for their expression stability using the geNorm and NormFinder statistical algorithms. Expression stability was assessed by qRT-PCR across 32 biological samples, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 47 publications
3
82
0
Order By: Relevance
“…Quantification of gene expression requires the use of appropriate reference genes and such references have been developed for some plant species [9,22,25,[43][44][45][46]. For rice, a number of genes have been used.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of gene expression requires the use of appropriate reference genes and such references have been developed for some plant species [9,22,25,[43][44][45][46]. For rice, a number of genes have been used.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha tubulin 5 gene (AhTUA5) was taken as a reference gene (Chi et al, 2012). Seven pairs of gene-specific primers (Table 2) were designed after analysis of the sequences of target genes.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…The alpha tubulin 5 (AhTUA5) gene was used as an internal reference control for total RNA input (Chi et al, 2012). As shown in Figure 5, these six genes displayed specific temporal and spatial expression patterns across different tissues and developmental stages.…”
Section: Tissue-specifi C Expression Patternsmentioning
confidence: 99%
“…Here, we found that the antisense expression of AhPEPC1 increased lipid accumulation and decreased the protein content in the seeds of peanuts. However, Wang et al (2012) showed that the inhibition of Atppc4 had no effects on the lipid accumulation or fatty acid composition of Arabidopsis seeds. One major reason may be that the transcription profiles of PEPC genes in the seeds of peanuts are different from those in Arabidopsis seeds.…”
Section: Discussionmentioning
confidence: 98%
“…A qRT-PCR analysis was performed using a LightCycler 2.0 instrument system (Roche, Germany). The α-tubulin 5 gene (AhTUA5) was selected as a reference gene (Chi et al, 2012). Six pairs of genespecific primers (Table 1) were designed after an analysis of the target gene sequences.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%